‘The Pandemic Played a Cruel Joke on Us’: The vulnerabilities of Kyrgyz women migrant workers in Russia during COVID-19 - Abdukadyrova, Lola; Studenko, Olga (Anti-Trafficking Review, 2023)
The COVID-19 pandemic affected various aspects of social and economic life across the world, with women and minorities especially bearing the brunt of its negative consequences. For Kyrgyz migrant women in Russia, this was further compounded by particularities of the low-wage or informal sectors where they worked. This article contributes to the scholarship on the impact of COVID-19 on migrant workers in destination countries. Drawing on data from 298 Kyrgyz women working in Russia, it explores women’s experiences with income, labour protections, freedom of movement, and violence in the workplace during the pandemic. It demonstrates that these experiences are caused by the intersection of gender and migration status. The article concludes with recommendations directed at the Kyrgyz government and civil society to improve the situation of Kyrgyz migrant women working in Russia.